Unbroken : a World War II story of survival, resilience, and redemption - Hillenbrand, Laura (New York : Random House, 2010)
A biography of Olympic runner and World War II bombardier, Louis Zamperini, who had been rambunctious in childhood before succeeding in track and eventually serving in the military, which led to a trial in which he was forced to find a way to survive in the open ocean after being shot down.
Library Journal, October 2010
Pub Weekly, October 2010
Booklist, November 2010
New York Times, November 2010
Kirkus Review, September 2010
Includes bibliographical references (p. [407]-457) and index.
Keywords: Zamperini, Louis, -- 1917-; World War, 1939-1945 -- Prisoners and prisons, Japanese; Prisoners of war -- United States -- Biography; Prisoners of war -- Japan -- Biography; World War, 1939-1945 -- Aerial operations, American; World War, 1939-1945 -- Campaigns -- Pacific Area; United States. -- Army Air Forces. -- Heavy Bombardment Group, 307th.; Long-distance runners -- United States -- Biography; Zamperini, Louis, -- 1917-; World War, 1939-1945 -- Prisoners and prisons -- Japan; Prisoners of war -- United States -- Biography; Prisoners of war -- Japan -- Biography; World War, 1939-1945 -- Aerial operations; World War, 1939-1945 -- Campaigns -- Pacific Area; United States. -- Army Air Forces. -- Heavy Bombardment Group, 307th.; Runners (Sports) -- Biography